Multidimensional Communication and Education Strategies in Handling Plagiarism in Higher Education: Cultural, Ethical, and Language Psychology Perspectives - Catur Wahyuningsih; Muh. Mashuri Masyhuda; Marya Yenny; Irwan Prayitno (Indonesian Interdisciplinary Journal of Sharia Economics)
Plagiarism is a major challenge to maintaining academic integrity in higher education. Three different approaches - culture, professional ethics, and communication psychology offer complementary insights to understand and address this phenomenon. This article reviews three key studies: Fatemi & Saito (2019), who highlighted unintentional plagiarism among international students; Jiang et al. (2013), who examined integrity and risk factors in the health sciences; and Brown et al. (2019), who discussed metaphorical framing in shaping students' perceptions of plagiarism. Based on this synthesis, this article proposes an integrative strategy based on cross-cultural education, the establishment of a professional code of ethics, and the constructive use of metaphors in academic communication.